POTENSI PENDAPATAN ASLI DESA DI KECAMATAN SOPPENG RIAJA (STUDI KASUS DESA PACCEKKE DAN DESA LAWALLU) - Arham, Arham; Abu, Rahmawati (Universitas Muhammadiyah Parepare, 2019)
This study aims to study the feasibility of the potential of Original Village Revenues (PADesa) in two villages (Desa Paccekke and Desa Lawallu) located in Soppeng Riaja District. The implementation of this research uses published data collection techniques (1) direct observation or monitoring of the research object. Data were analyzed using qualitative analysis methods, the method offered to provide a complete picture of the subject under discussion. Percentage of Original Income in Pacceke Village only contributed 14.9 million rupiah (0.22%), where the highest percentage was revenue originating from the self-help budget, participation and mutual assistance. Lawallu Village community participation in the implementation of development and village development is more visible, this is based on the Village Original Income Value (PADesa) sourced from the results of operations, self-help, participation and mutual cooperation, and other legitimate village original income of 25.75 million rupiah (0.32%). The original income of Pacceke Village and Lawallu Village is still relatively small based on the PADesa obtained in 2014-2018.